Foam concrete main material - QIN JIANLU; SHI YITONG; FAN SHUANGSHUANG; ZHANG LEI; ZHANG JIANHUA; LI KE; LIU HAIQING (2017)
The invention discloses a foam concrete main material. The foam concrete main material is prepared from the following raw materials in percentage by weight: 10 to 46 percent of cement clinker, 50 to 85 percent admixture, 0 to 10 percent of calcined lime, 2 to 6 percent of glass fiber, 0 to 1 percent of dispersible latex, 0.3 to 0.5 percent of coagulation accelerator, 0.2 to 0.4 percent of water reducing agent and 0.1 to 1 percent of foam stabilizer. By adopting the foam concrete main material provided by the invention, the problems of unstable quality and insufficient strength of obtained foam concrete caused by taking a cement raw material as a main material in the conventional foam concrete are solved. 本发明公开了种泡沫混凝土主材料，包括以下重量百分比的原料制成：水泥熟料10%-46%、掺合料50%-85%、生石灰0-10%、玻璃纤维2%-6%、可分散性乳胶粉0-1%、促凝剂0.3%-0.5%、减水剂0.2%-0.4%和稳泡剂0.1%-1%。本发明提供的泡沫混凝土主材料，解决了目前泡沫混凝土以水泥原料为主材料，使所得泡沫混凝土质量不稳定、强度不够的问题。